2006
DOI: 10.1099/jmm.0.46271-0
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired methicillin-resistant Staphylococcus aureus pyomyositis in an intravenous drug user

Abstract: Pyomyositis is a disease of abscess formation deep within large striated muscles. Outside of the tropics it is a rare disease which occurs mainly in certain patient populations such as the immunosuppressed or intravenous drug users (IDUs). A case of community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) pyomyositis in an IDU is described. The incidence of both CA-MRSA and pyomyositis is currently increasing. To the authors' knowledge this is the first reported case of CA-MRSA pyomyositis in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…Therefore, our study demonstrates that valid concerns were raised by recent studies reporting the emergence of community-acquired oxacillinresistant S. aureus as an important cause of pyomyositis [17,28,32]. Empiric antibiotic therapy should provide coverage for oxacillin-resistant S. aureus.…”
Section: Anaerobes 4 10%mentioning
confidence: 88%
See 2 more Smart Citations
“…Therefore, our study demonstrates that valid concerns were raised by recent studies reporting the emergence of community-acquired oxacillinresistant S. aureus as an important cause of pyomyositis [17,28,32]. Empiric antibiotic therapy should provide coverage for oxacillin-resistant S. aureus.…”
Section: Anaerobes 4 10%mentioning
confidence: 88%
“…Literature on pyomyositis points out that S. aureus is the most common organism [4,12,13,15], however, recent studies have reported infections due to Gram-negative organisms [15,34,36], and oxacillin-resistant S. aureus [17,28,32]. We determined the rate of such infections due to oxacillin-resistant Staphylococcus aureus and Gram-negative organism infections, and asked whether the occurrence of oxacillinresistant pathogens increased during the study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parenteral drug use is well known for carrying the risk of transmission of several infectious diseases [26][27][28][29]. Wound botulism is of special importance for two reasons : first, the clinical course is often severe and life-threatening, and second, the rarity of the disease renders diagnosis difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Nadir görülmesi ve non-spesifik klinik özellikleri nedeniyle tanısı sıklıkla gecikir [20]. Klinik seyrin ilk aşaması invaziv faz olup enfeksiyonun ilk 2-3 haftasında görülür.…”
Section: Miyozit Piyomiyozitunclassified